A Question of Authenticity: Status Quo Bias and the International Energy Agency's World Energy Outlook. Issue 5 (19th October 2016) - Gaede, James; Meadowcroft, James
Abstract: Over the past decade, transition scholars have argued that images of the future (of what sort of change is possible or probable, desirable or undesirable) play a critical role in societal transitions, and there is a long-standing tradition of analysis that points out the political significance of visions of the future. This article explores the politics of the future in sustainability transitions by looking at controversy surrounding a prominent global energy future report—the International Energy Agency's World Energy Outlook —between 1998 and 2008/2009. A key theme of this controversy was that the Outlook's record on global oil supply projections demonstrated a bias towards the preservation of the status quo. Based on research interviews conducted with key participants in this controversy, and a review of Outlooks produced between 1998 and 2008, we explore the main 'sites of contention' in the allegation of bias from both an 'internal' (sympathetic) and an 'external' (critical) perspective. We argue that the politics of bias have less to do with one's relationship vis-à-vis the preservation of the regime, and more to do with a question concerning the speaker's authenticity.